Responses of primary human nasal epithelial cells to EDIII-DENV stimulation: the first step to intranasal dengue vaccination - Nattika Nantachit (2017)
Background: About half of the world’s population are living in the endemic area of dengue viruses implying that a rapid-mass vaccination may be required. In addition, a major target of dengue vaccine are children, thus, a needle-free administration is more attractive. These problems may be overcome by the alternative route of vaccination such as topical, oral and intranasal vaccination. Here, we investigated the possibility to deliver a dengue immunogen intranasally, a painless route of vaccination. The tested immunogen was the domain III of dengue serotype-3 E protein (EDIII-D3) loaded into trimethyl chitosan nanoparticles (EDIII-D3 TMC NPs). The primary human nasal epithelial cells, HNEpCs, were used as an in vitro model for nasal responses. Results: At tested concentrations, EDIII-D3 TMC NPs not only exerted no detectable toxicity toward HNEpC cultures but also efficiently delivered EDIII-D3 immunogens into HNEpCs. Moreover, HNEpCs quickly and strongly produced proinflammatory cytokines (IL-1β, IL-6, TNF-α), type-I IFN, the growth factors (GM-CSF, IL-7), the chemokines (MCP-1, MIP-1β, IL-8), Th1-related cytokines (IL-2, IL-12p70, IL-17, IFN-γ) and Th2-related cytokine (IL-4) in response to EDIII-D3 TMC NPs treatment. Conclusions: A potential mucosal delivery system for dengue immunogens was revealed and found to stimulate a strong local innate antiviral response which possibly leading to a systemic adaptive immunity.